Contrast media dose adjustment to allometric parameters of body mass in multiphasic CT of the liver: A comparison of different metrics. Issue 141 (August 2021) - Janek, Elmar; Edl, Dominik; Taflinski, Adrian; Talakic, Emina; Adelsmayr, Gabriel; Janisch, Michael; Igrec, Jasminka; Quehenberger, Franz; Fuchsjäger, Michael; Schöllnast, Helmut
Highlights: Lean body weight correlates with vascular and parenchymal enhancement. Abstract: Purpose: To assess correlations of lean body weight (LBW) calculated with various formulas, total body weight (TBW), body height (BH), body mass index (BMI), body surface area (BSA) and fat-free mass (FFM) with vascular and parenchymal enhancement in multiphasic CT of the liver. Method: Thirty consecutive patients underwent multiphasic CT of the liver using constant iodine dose and flow rate. Contrast enhancement of aorta, portal vein and liver was calculated by measuring mean vascular and parenchymal attenuation in pre-contrast and post-contrast phases. Correlations of TBW, BH, BMI, BSA, FFM, and LBW (calculated with formulas of Boer, Hume, James and Green&Duffull ) with enhancement were tested using Spearman's correlation coefficient. The method of Fieller et al. was used to calculate 95 % confidence intervals. A p-value ≤ 0.05 was considered statistically significant. Results: Aortal enhancement correlated strongly with TBW, BSA, LBW Boer and LBW Hume and moderately with BH, BMI, FFM, LBW James and LBW Green&Duffull . Liver enhancement in the late arterial phase correlated moderately with TBW, FFM, LBW Boer, LBW Hume and LBW Green&Duffull and weakly with BSA. Liver enhancement in the portal venous phase correlated strongly with TBW, BSA, FFM, LBW Boer, LBW Hume and LBW Green&Duffull, whereby overlap of the 95 % CI graphs demonstrated that the differences in the correlation coefficients were not statistically significant. Liver enhancement in the delayed phase correlated moderately with BH but did not correlate significantly with any other parameter. Conclusion: Regardless of the form used for calculation, LBW did not correlate statistically significantly stronger than TBW with vascular or parenchymal enhancement of the liver.